Plant diversity and dynamics in chalk quarries on the islands of Rügen and Wolin (Western Pomerania/Germany and Poland) - König, Peter (Biodiversity: Research and Conservation, 2017)
Chalk mining industry in Western Pomerania reflects a history of almost 300 years, and has left behind a typical post-mining landscape. Thus, more than 50 formerly exploited areas are known on the islands of Rügen and Wolin. Historical quarry sizes range from 0.1 to 42 hectares, the median is 1.3. Chalk quarries are recolonised by a wide range of species and develop attractive and species-rich communities. To the extent that recolonisation progresses, they act as refugia for rare or local species. Currently, a total of 543 vascular plant species are found in these chalk quarries. Species number ranges from 97 to 218 in thoroughly studied sites, with a median of 138. Of the total floristic inventory, 67% are indigenous species, 18% are archaeophytes and 12% neophytes. Quarries abandoned long ago and remotely situated are home to nearly 90% indigenophytes, whereas those quarries close to settlements or with easy access are tendentially characterised by numerous synanthropic plants. 100 species overall (= 18.4%) belong to Red List categories of Mecklenburg-Western Pomerania. In 22 quarries studied in more detail, Red List percentages show a spectrum from 3.7 to 23.5%, and higher values are found in sites with open habitats and considerable biotope diversity. Among vegetation types, the anthropo-zoogenic heathland and grassland harbours 40% Red List species and occupies the first place concerning nature conservation aspects. A noteworthy percentage of endangered plants is found in fresh-water and bog vegetation, as some quarries are in contact with the aquifer. Succession was and is the impetus for vegetation development. A transect exemplarily demonstrates the vegetation zonation within a chalk quarry and distinguishes headslope, backslope, and footslope and the quarry floor. The respective plant communities are classified into Cornus sanguinea bush stage, Picris hieracioides-Daucus carota community, and basiphilous mesoxerophytic grassland.